The Relationship Between Atrial Fibrillation and Intestinal Flora With Its Metabolites - Lu, Dasheng; Zou, Xinyue; Zhang, Hongxiang (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF) is characterized by high morbidity and disability rate. The incidence of AF has rapidly increased due to increased aging population, causing a serious burden on society and patients. Therefore, it is necessary to determine the prevention and treatment of AF. Several studies have assessed the occurrence, development mechanism, and intervention measures of AF. The human gut has several non-pathogenic microorganisms forming the gut flora. The human gut microbiota plays a crucial role in the construction and operation of the metabolic system and immune system. Emerging clinical studies and basic experiments have confirmed that intestinal flora and its metabolites have a role in some metabolic disorders and chronic inflammatory diseases. Moreover, the gut microbiota has a role in cardiovascular diseases, such as hypertension and heart failure. However, the relationship between AF and gut microbiota is unclear. This review summarizes the relevant literature on the relationship between AF and intestinal flora with its metabolites, including Trimethylamine N-Oxide, short-chain fatty acids, lipopolysaccharide and bile acids. Therefore, this review may enhance further development of related research.